Left ventricular function in beta thalassaemia major. Issue 7 (July 1989) - Lau, K C; Li, A M; Hui, P W; Yeung, C Y
Abstract : The left ventricular dimension and posterior wall dynamics were studied by computer assisted analysis of M mode echocardiography in 25 normal children (group 1) and 32 transfusion dependent children with beta thalassaemia major who had no evidence of heart failure (group 2). Twenty seven of those in group 2 remained well but five died of cardiac decompensation within 12 months. Compared with group 1, the left ventricular fractional shortening and ejection fraction were normal in those in group 2 who survived but diminished in those who died. Evaluation of left ventricular dimension and posterior wall dynamics during systole (peak shortening rate, peak velocity of circumferential fibre shortening, and peak posterior wall thickening rate) showed similar findings in that only the group who died had abnormal values. The left ventricular dimension and posterior wall diastolic dynamics (peak relaxation rate, normalised peak relaxation, peak wall thinning, and normalised peak wall thinning rate), however, showed progressively slower rates in all the children in group 2. The findings suggest that left ventricular diastolic dysfunction occurs early in myocardial impairment in patients with beta thalassaemia major. When there are abnormalities in both diastole and systole, the myocardial impairment is advanced and the prognosis is poor.